Parsonage-Turner Syndrome Following COVID-19 Vaccination: Clinical and Electromyographic Findings in 6 Patients - Shields, Lisa B.E.; Iyer, Vasudeva G.; Zhang, Yi Ping; Burger, John T.; Shields, Christopher B. (Case reports in neurology, 2022)
Parsonage-Turner syndrome (PTS) following COVID-19 infection or vaccination is rare. The pathophysiology may involve an immune-mediated inflammatory reaction against brachial plexus nerve fibers in a genetically predisposed individual. We describe the clinical and electromyographic features of 6 patients presenting with the clinical picture of PTS following COVID-19 vaccination. All patients were referred for electromyographic studies to evaluate the acute onset of pain in the shoulder girdle/upper limb accompanied by muscle weakness in the distribution of one or more branches of the brachial plexus. Each patient had received the COVID-19 vaccine within a few weeks prior to the onset of symptoms. Patients underwent detailed neurological examinations followed by nerve conduction and EMG studies. The patients developed symptoms after a mean duration of 17 days (5 days–8 weeks) after receiving the COVID-19 vaccine. The initial symptom was pain in the shoulder girdle/upper limb, followed within days by muscle weakness. Physical examinations and EMG studies showed upper trunk brachial plexopathy in 2 patients, lower trunk plexopathy in 1 patient, posterior cord brachial plexopathy in 1 patient, and anterior/posterior interosseous nerve involvement in 2 patients. All patients either improved or attained complete resolution of the arm pain at follow-up. Three (50%) patients did not have any improvement in the arm/hand weakness, while 3 (50%) patients had some recovery in strength. PTS may occur after the COVID-19 vaccine and should be suspected in patients with symptoms and signs suggestive of acute brachial plexopathy. Studies of a larger series may provide insight into predisposing factors.